Developing the role of patients as teachers: literature review - Wykurz, Geoff (BMJ, 2002)
OBJECTIVES: To identify the roles and settings in which patients participate as teachers in medical education and the benefits to learners, their educational institutions, and participating patients. DESIGN: Review of publications from 1970 to October 2001 providing descriptions, evaluations, or research of programmes involving patients as teachers in medical education. DATA SOURCES: 1848 references were identified from various electronic databases. Applying inclusion criteria to abstracts generated 100 articles, from which 23 were selected after independent scrutiny. RESULTS: 13 articles discussed the role of patients in teaching physical examination skills, mostly musculoskeletal examination. Patients also taught pelvic and male genitorectal examination skills. Teaching roles varied, and 19 articles referred to patients' involvement as assessors. 18 articles described patients' training, with some patients being assessed. Reports of learners' experiences were all positive, many valuing the insights and confidence gained from practising skills on patients in a teaching role. Some learners preferred being taught by trained patients rather than doctors. Patients who were consulted enjoyed their teaching role. Several articles commented on the high quality of patients' teaching. Remuneration varied from payment of expenses to an hourly rate. Motivation for recruiting patients included the desire to reduce costs and the value attributed to the consumers' perspective. CONCLUSION: Involving patients as teachers has important educational benefits for learners. Patients offer unique qualities that can enhance the acquisition of skills and change attitudes towards patients.